An evaluation of a morphine public health programme for cancer and AIDS pain relief in Sub-Saharan Africa - Harding Richard; Logie Dorothy E (BMC, 2005)
Abstract Background Despite growing HIV and cancer prevalence in Sub-Saharan Africa, and WHO advocacy for a public health approach to palliative care provision, opioid availability is severely limited. Uganda has achieved a morphine roll-out programme in partnership with the Ministry of Health. This study aimed to evaluate that programme by identifying challenges to implementation that may inform replication. Methods A multi-methods protocol appraised morphine regulation, storage, prescribing, and consumption in three phases: key informant interviews throughout the opioid supply chain, and direct observation and audit of clinical practice. Results Regulation had achieved its goal of preventing misuse and leakage from the supply chain. However, the Government felt that relaxation of regulation was now appropriate. Confusion and complexity in storage and authorisation rules led to discontinuation of opioid pain management at the patient level and also wasted service time in trying to obtain supplies to which they were entitled. Continued neglect to prescribe among clinicians and public fear of opioids led to under prescribing, and clinical skills showed some evidence of need for improvement with respect to physical assessment and follow-up. Conclusion The Ugandan programme offers a successful model for both advocacy and Governmental support in achieving opioid roll-out across health districts. Despite initial concerns, abuse of opioids has not been evident. Further work is required to ensure that available supplies of opioids are prescribed to those in need, and that clinical standards are met. However, the programme for roll-out has proved a useful model to expand opioid availability as the first step in improving patient care, and may prove a useful template for other Sub-Saharan African countries.